2010
DOI: 10.1103/physrevstab.13.080702
|View full text |Cite
|
Sign up to set email alerts
|

Electron beam energy spread measurements using optical klystron radiation

Abstract: In accelerators, the electron beam longitudinal dynamics critically depend on the energy distribution of the beam. Noninvasive, highly accurate measurement of the energy spread of the electron beam in the storage ring remains a challenge. Conventional techniques are limited to measuring a relatively large energy spread using the energy spread induced broadening effect of radiation source size or radiation spectrum. In this work, we report a versatile method to accurately measure the electron beam relative ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…With proper cross-calibration, the study of the FEL power is based upon the measured extracted FEL power from the upstream FEL mirror. The direct FEL power P FEL can be written as [51][52][53][54][55][56]…”
Section: Power Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…With proper cross-calibration, the study of the FEL power is based upon the measured extracted FEL power from the upstream FEL mirror. The direct FEL power P FEL can be written as [51][52][53][54][55][56]…”
Section: Power Controlmentioning
confidence: 99%
“…where α is a numerical factor depending on the undulator configuration and FEL operational conditions; P syn is the total synchrotron radiation power emitted by the electron bunch in the entire storage ring; σ E;FEL and σ E;0 are the rms relative electron beam energy spread with FEL turned on and off, respectively. In the microwave instability region with large enough bunch current and/or with FEL lasing to increase the electron beam energy spread, the electron beam energy spread and bunch length are found to be related in a simple manner due to the longitudinal phase space rotation [55]:…”
Section: Power Controlmentioning
confidence: 99%
“…A few published reviews on Compton γ-ray beams and some of the aforementioned facilities are found in [261][262][263][264][265]. Among these Compton CGS facilities, the High Intensity Gamma-ray Source (HIGS) at Duke University is the first dedicated Compton gamma-ray facility employing as the photon driver a high intra-cavity power free-electron laser (FEL) [266][267][268][269][270]. The HIGS facility is a high-flux, nearly monochromatic, and highly polarized CGS (with both linear and circular polarizations) covering a wide range of energies from about 1 to 100 MeV.…”
Section: Introduction To Compton Gamma-ray Sourcesmentioning
confidence: 99%
“…The accuracy of this method was improved by a new fitting method in Ref. [20]. The relative energy spread was measured from 6 Â 10 À4 to 6 Â 10 À3 with an overall uncertainty of less than 5% in the Duke storage ring based on this method.…”
Section: Introductionmentioning
confidence: 99%